IMPROVING THE STUDENTS’ VOCABULARY MASTERY BY USING WORD SQUARE MEDIA - Ian Harum Prasasti; Yasmika Baihaqi; Bambang Eko Siagiyanto; Fitri Palupi Kusumawati; Winda Amilia (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
The purpose of this research is to find out whether using word square media can improve the vocabulary mastery of the eleventh grade students of SMK Negeri 3 Metro. In this study, researchers conducted classroom action research (CAR) which was carried out in three cycles. Each cycle consists of planning, acting, observing and reflecting. The subjects of this study were 32 students of eleventh grade at SMK Negeri 3 Metro. In collecting data, researchers used pre-test, post-test 1, post-test 2, post-test 3, observing, interview, and questionnaire. The results of the study show that using Word square media can improve stu-dents’ vocabulary mastery at eleventh grade of SMK Negeri 3 Metro, this can be seen in the progress of the pre-test and post-test cycle 1 to cycle 3. the average of pre-test score was 42.31% and the post-test in cycle 1 was 61.37%, the average value in post-test 2 was 75.40% and the average score in cycle 3 was 81.37%. pre-test and post-test cycle 1 to post-test cy-cle 3 there was an increase of 5.97%. it means that the results of the post test have reached indicators of success that can be achieved on the results of this post-test. Students responses in using word square media that have been done can be seen that 93.45% of students gave respones very positive in learning using word square learning media and word square media can be said to be practical and easy to use for students, this can be seen from the enthusiasm of students and their spirits at the first time in using word square media.